Income convergence during the crisis: did EU funds provide a buffer? - Silvia Merler (Bruegel, 2016)
Economic convergence is at the heart of European Union integration. The importance of this objective has not diminished over time, and it is especially relevant in light of the economic crisis that has exacted a heavy toll on EU countries and created scepticism about the merits of EU policies. The author looks at how economic convergence evolved in different regions during the crisis and assess the role played by those funds that are provided to the more disadvantaged regions, with the aim of facilitating their convergence to average EU income levels. Both an absolute and a conditional convergence analysis were run, using regional data on per capita GDP in purchasing power standard. Convergence continued during the crisis for the EU as a whole, although at a slower pace, but for regions in the EU14, and especially in the euro area, convergence appears to have stopped during the crisis, or even switched to a divergence path. The funds' eligibility rules were exploited in order to construct a quasi-experimental framework, based on comparable treatment and control group of regions. Regional policy played an important role in limiting the effects of the crisis at the region level, by providing an important anchor for convergence in those regions that benefited from the funds.
Keywords: 330